2005
DOI: 10.1016/j.chembiol.2005.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Metabolism of Ergosterol by Cytochrome P450scc to Biologically Active 17α,24-Dihydroxyergosterol

Abstract: We demonstrate the metabolism of ergosterol by cytochrome P450scc in either a reconstituted system or isolated adrenal mitochondria. The major reaction product was identified as 17alpha,24-dihydroxyergosterol. Purified P450scc also generated hydroxyergosterol as a minor product, which is probably an intermediate in the synthesis of 17alpha,24-dihydroxyergosterol. In contrast to cholesterol and 7-dehydrocholesterol, cleavage of the ergosterol side chain was not observed. NMR analysis clearly located one hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 37 publications
2
78
0
Order By: Relevance
“…Most recently, it has been uncovered that the classical enzyme of steroidogenesis cytochrome P450scc can also cleave the side chain of 7-DHC to produce 7-dehydropregnenolone (7-DHP) identifying a novel metabolic pathway producing 5,7 diene hydroxysteroids that after UVB exposure could generate secosteroidal vitamin D-like (VitDL) products [137,138]. Moreover, vitamin D3, ergosterol (provitamin D2) and vitamin D2 are additionally metabolized by the same P450scc producing hydroxyderivatives [42,139,140], some of which induce differentiation and inhibit proliferation of skin cells [139,141]. Thus, new family of vitamin D derivatives was identified that could be tested for its potential antimelanoma activity.…”
Section: Glucocorticoids Receptorsmentioning
confidence: 99%
“…Most recently, it has been uncovered that the classical enzyme of steroidogenesis cytochrome P450scc can also cleave the side chain of 7-DHC to produce 7-dehydropregnenolone (7-DHP) identifying a novel metabolic pathway producing 5,7 diene hydroxysteroids that after UVB exposure could generate secosteroidal vitamin D-like (VitDL) products [137,138]. Moreover, vitamin D3, ergosterol (provitamin D2) and vitamin D2 are additionally metabolized by the same P450scc producing hydroxyderivatives [42,139,140], some of which induce differentiation and inhibit proliferation of skin cells [139,141]. Thus, new family of vitamin D derivatives was identified that could be tested for its potential antimelanoma activity.…”
Section: Glucocorticoids Receptorsmentioning
confidence: 99%
“…Thus, when topically applied, ergosterol may serve as a substrate for P450scc with potential implications in therapy of skin hyperproliferative or inflammatory disorders. In fact previous experiments indicate that dihydroxyergosterol metabolites of bovine P450scc can inhibit proliferation of immortalized human epidermal keratinocytes (Slominski et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that bovine P450scc can hydroxylate ergosterol producing 17␣,24-dihydroxyergosterol as the major product with no evidence for cleavage of the side chain (Slominski et al, 2005b). Having the same side chain as ergosterol, vitamin D 2 is metabolized by bovine P450scc to 20-hydroxyvitamin D 2 , 17,20-dihydroxyvitamin D 2 , and 17,20,24-trihydroxyvitamin D 2 (Nguyen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction involves removal of the side chain of cholesterol via production of enzyme-bound intermediates, 22R-hydroxycholesterol and 20α,22R-dihydroxycholesterol (Hume et al, 1984;Lambeth et al, 1982;Tuckey, 1990Tuckey, , 2005. Cytochrome P450scc can also metabolize vitamin D3 (D3) and vitamin D2 (D2), as well as their precursors 7-dehydrocholesterol and ergosterol (Guryev et al, 2003;Slominski et al, 2004Slominski et al, , 2005aSlominski et al, ,b, 2006Tuckey et al, 2008). Our most recent study shows that P450scc can hydroxylate D3 at carbons 17, 20 and 23 (Tuckey et al, 2008).…”
Section: Introductionmentioning
confidence: 99%